2016
DOI: 10.1002/pros.23261
|View full text |Cite
|
Sign up to set email alerts
|

Glyoxalase 2 Is Involved in Human Prostate Cancer Progression as Part of a Mechanism Driven By PTEN/PI3K/AKT/mTOR Signaling With Involvement of PKM2 and ERα

Abstract: Targeting glyoxalases metabolic pathway may represent a strategy to selectively inhibit advanced PCa. Prostate 77:196-210, 2017. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
60
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(71 citation statements)
references
References 54 publications
3
60
0
1
Order By: Relevance
“…Notably, a distinctly high activity of Glo1 was observed in 22 out of 22 PCa specimens and none to little activity in 10 out of 10 non-malignant specimens. Although preliminary, these results opened new pathways of investigation towards the study of Glo1 expression, either at mRNA, protein or functional level, in PCa tissues and normal counterparts or in differently aggressive and invasive PCas [36,37,[52][53][54][55]. Overall, these studies strongly indicated Glo1 as a novel important protein involved in PCa genesis and progression, thus suggesting an oncogenic role for this enzyme in this neoplasm.…”
Section: Glo1mentioning
confidence: 95%
See 4 more Smart Citations
“…Notably, a distinctly high activity of Glo1 was observed in 22 out of 22 PCa specimens and none to little activity in 10 out of 10 non-malignant specimens. Although preliminary, these results opened new pathways of investigation towards the study of Glo1 expression, either at mRNA, protein or functional level, in PCa tissues and normal counterparts or in differently aggressive and invasive PCas [36,37,[52][53][54][55]. Overall, these studies strongly indicated Glo1 as a novel important protein involved in PCa genesis and progression, thus suggesting an oncogenic role for this enzyme in this neoplasm.…”
Section: Glo1mentioning
confidence: 95%
“…Overexpression of Glo1 in PCa cells would aim at maintaining low intracellular levels of the glycolysis-derived cytotoxic metabolite MG, as a survival defense strategy. Indeed, in vitro studies performed with PCa cell lines, causatively demonstrated this role [24,25,36], in addition to pointing out a pro-survival function for this protein by eluding apoptosis in a mechanism involving the desensitization of NF-kB pathway [25]. Only one study, based on the proteomic analysis of normal and malignant prostate tissues, identified Glo1 among the proteins lost in PCa [56].…”
Section: Glo1mentioning
confidence: 99%
See 3 more Smart Citations